Suicide and Youth: Risk Factors - Bilsen, Johan (Frontiers in Psychiatry, 2018)
From the perspective of public mental health, suicide among young people is a main issue to address through effective preventive measures. Therefore it is important to gain as much insight as possible in the risk factors contributing to suicidal behavior in youth. Several population-based psychological autopsy studies of suicides have been conducted, involving interviews with key informants and examination of records, as well as follow-up studies of people who have attempted suicide, revealing important information about the risk factors for youth suicide. In this mini review we give a short overview of the most important risk factors as established by scientific research in this domain. Numerous factors can contribute to suicide, and ultimately each suicide is caused by a highly unique, dynamic and complex interplay of genetic, biological, psychological and social factors. Nevertheless, it is possible to identify different types of factors that are clearly associated with an increased risk of youth suicide. Mental disorders, previous suicide attempts, specific personality characteristics, genetic loading and family processes in combination with triggering psychosocial stressors, exposure to inspiring models and availability of means of committing suicide are key risk factors in youth suicide and are highly relevant with regard to the development of prevention strategy plans.